Assessment of Canadian perinatal mental health services from the provider perspective: Where can we improve? - Hicks, Laurel M.; Ou, Christine; Charlebois, Jaime; Tarasoff, Lesley; Pawluski, Jodi; Roos, Leslie E.; Hooykaas, Amanda; Fairbrother, Nichole; Carter, Michelle; Tomfohr-Madsen, Lianne (Frontiers in Psychiatry, 2022)
Purpose: Perinatal mental health disorders are common, and rates have increased during the COVID-19 pandemic. It is unclear where providers may improve perinatal mental health care, particularly in countries lacking national guidelines, such as Canada. Methods: A cross-sectional survey of perinatal health providers was conducted to describe the landscape of perinatal mental health knowledge, screening, and treatment practices across Canada. Providers were recruited through listservs, social media, and snowball sampling. Participants completed an online survey that assessed their perinatal mental health training, service provision types, their patient wait times, and treatment barriers, and COVID-19 pandemic-related impacts. Results: A total of 435 providers completed the survey, including physicians, midwives, psychologists, social workers, nurses, and allied non-mental health professionals. Most (87.0%) did not have workplace mandated screening for perinatal mental illness but a third (66%) use a validated screening tool. Many (42%) providers stated their patients needed to wait more than 2 months for services. More than half (57.3%) reported they did not receive or were unsure if they received specialized training in perinatal mental health. Most (87.0%) indicated there were cultural, linguistic, and financial barriers to accessing services. Over two-thirds (69.0%) reported the COVID-19 pandemic reduced access to services. Conclusions: Survey findings reveal significant gaps in training, screening tool use, and timely and culturally safe treatment of perinatal mental health concerns. There is critical need for coordinated and nationally mandated perinatal mental health services in Canada to improve care for pregnant and postpartum people.